Frequency of parametric X-ray radiation - Shchagin, A.V.; Kube, G. (Problems of Atomic Science and Technology, 2023)
The exact solution of the equation for the frequency of parametric X-ray radiation (PXR) of relativistic charged particles moving in a crystal is obtained and compared to the approximate solution. It is found that the exact solution is in good agreement with the approximate one and that the approximate PXR frequency solution is practically correct for a comparison to experimental data. Отримано точний розв’язок рівняння частоти параметричного рентгенівського випромінювання релятивістських заряджених частинок, що рухаються в кристалі, та порівняно з наближеним розв’язком. Встановлено, що точний розв’язок добре узгоджується з приблизним рішенням і що приблизний частотний розв’язок практично коректний для порівняння з експериментальними даними.